We want to figure out if f(x) and g(x) are inverses of each other.
![f(x)=3x\text{ and }g(x)=(x)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/dwrt228twh28fcpd29gozro8uiau0mn5fk.png)
We have to find f(g(x)) and g(f(x)).
![f(g(x))=3((x)/(3))=x](https://img.qammunity.org/2023/formulas/mathematics/college/wdkm6s04uuu9zu7pyr4pwfm7syb16xukwc.png)
And;
![g(f(x))=((3x))/(3)=x](https://img.qammunity.org/2023/formulas/mathematics/college/4ky6dy7xtucq7bh31jtxfxz8yy9hnows0t.png)
Now, since ;
![f(g(x))=g(f(x))](https://img.qammunity.org/2023/formulas/mathematics/college/j0n93la4yquzp82oo19q61nn77xepcip5w.png)
We can conclude that;
![f(x)\text{ and g(x) are inverses of each other}](https://img.qammunity.org/2023/formulas/mathematics/college/60m3pxrc48xcdx3dqrmua927ywk79236qk.png)
b.
![f(x)=2x+3\text{ and }g(x)=(x-3)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/vlv8gw1bx94ktz8gqc3soi52a4q45dnwyl.png)
Let us compute f(g(x)) and g(f(x)) to see if these two functions are inverses of each other.
![\begin{gathered} f(g(x))=2((x-3)/(2))+3=x-3+3 \\ f(g(x))=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xphluay77dy6mct4mdnzze5f6k0az9ygj9.png)
And;
![\begin{gathered} g(f(x))=(2x+3-3)/(2)=(2x)/(2) \\ g(f(x))=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1eytu3hiwjj0bu1xc99bx6kop1do2pli76.png)
Now, since ;
![f(g(x))=g(f(x))](https://img.qammunity.org/2023/formulas/mathematics/college/j0n93la4yquzp82oo19q61nn77xepcip5w.png)
We can conclude that;
![f(x)\text{ and g(x) are inverses of each other}](https://img.qammunity.org/2023/formulas/mathematics/college/60m3pxrc48xcdx3dqrmua927ywk79236qk.png)